2020
DOI: 10.1186/s40478-020-01089-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal alcohol exposure is a leading cause of interneuronopathy in humans

Abstract: Alcohol affects multiple neurotransmitter systems, notably the GABAergic system and has been recognised for a long time as particularly damaging during critical stages of brain development. Nevertheless, data from the literature are most often derived from animal or in vitro models. In order to study the production, migration and cortical density disturbances of GABAergic interneurons upon prenatal alcohol exposure, we performed immunohistochemical studies by means of the proliferation marker Ki67, GABA and ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 67 publications
3
19
0
Order By: Relevance
“…Overall, the transcriptome of interneuron clusters that were present in this region of the developing cerebral cortex were among the least affected by alcohol exposure, in contrast to significant effects on interneurons observed in other PAE models (Marguet et al, 2020;Skorput et al, 2015). However, one interneuron cluster, cluster #11, was specifically affected by PAE in both males and females, but in opposite directions.…”
Section: Pae Results In Distinct Sex-specific Patterns Of Gene Expression Dysregulation Primarily In Migrating Cell Populationsmentioning
confidence: 84%
“…Overall, the transcriptome of interneuron clusters that were present in this region of the developing cerebral cortex were among the least affected by alcohol exposure, in contrast to significant effects on interneurons observed in other PAE models (Marguet et al, 2020;Skorput et al, 2015). However, one interneuron cluster, cluster #11, was specifically affected by PAE in both males and females, but in opposite directions.…”
Section: Pae Results In Distinct Sex-specific Patterns Of Gene Expression Dysregulation Primarily In Migrating Cell Populationsmentioning
confidence: 84%
“…Since oligodendrocyte development and myelin are a target of alcohol, the disruption of oligodendrocyte differentiation and of myelination process is very likely responsible for inadequate establishment of neuronal networks and inefficient conduction of neuronal signals. Disruption of oligodendrocyte generation and differentiation, together with GABA interneuronopathy that we previously identified [ 28 ], most likely contribute to developmental encephalopathy and subsequent life-long neuro-behavioural disabilities.…”
Section: Discussionmentioning
confidence: 99%
“…As previously reported [ 28 ], the brains used in this study belong to the collection which has been declared to the French Ministry of Health (collection number DC-2015-2468, cession number AC-2015-2467, located in A. Laquerrière’s Pathology Laboratory, Rouen University hospital). In each case, the parents gave their informed written consent for neuropathological studies.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous animal models have shown that interneurons are sensitive to EtOH in various brain regions, including the striatum, medial prefrontal cortex, cerebral cortex, orbitofrontal cortex, and hippocampus (Bird et al, 2018; De Giorgio et al, 2012; Hamilton et al, 2017; Kenton et al, 2020; Madden et al, 2020; Sadrian et al, 2014; Saito et al, 2018; Smiley et al, 2015). Consequently, developmental EtOH exposure has previously been characterized as resulting in “interneuronopathy” (Bird et al, 2018; Madden et al, 2020; Marguet et al, 2020; Skorput et al, 2015; Smiley et al, 2015). However, the effects of EtOH exposure are not always inhibitory.…”
Section: Discussionmentioning
confidence: 99%